A Program Evaluation of a Summer Research Training Institute for American Indian and Alaska Native Health Professionals. - Zaback, Tosha; Becker, Thomas M.; Dignan, Mark B.; Lambert, William E. (American Indian Culture & Research Journal, 2010)
The writers discuss a unique summer program to train American Indian/Alaskan Native (AI/AN) health professionals in a range of health research–related skills. They explain that the Summer Research Training Institute for AI/AN Health Professionals is modeled on their successful Native Researchers' Cancer Control Training Program, which was founded in 1995. They explain that their objective is to offer training to health professionals in the conduct of scientific research, including epidemiology, data management, statistical analysis, program evaluation, cost-benefit analysis, community-based participatory research, grant writing, and program/policy development, so as to enhance research capacities and increase the number of qualified AI/AN principal investigators in Indian country. They present a brief description of the training program and an assessment of its process and outcomes.